Evaluation of Tuberculosis Risk under Interleukin-1 Inhibitor Agents in Patients with Autoinflammatory Diseases: Experience from a Region with Moderate Tuberculosis Prevalence - Karakaş, Özlem; Dogan, İsmail; Güven, Serdar Can; Erel, Şule; Erten, Sukran (Aktuelle Rheumatologie, 2023)
Background We aimed to investigate the rate of TBC reactivation in patients with autoinflammatory conditions who had been followed up under treatment with IL-1 antagonists in our clinic. We further aimed to evaluate whether latent TBC screening and isoniazid prophylaxis before IL-1 inhibitor treatment is beneficial in the prevention of reactivation.Patients and Methods This study was designed as a cross-sectional and observational study. It received the approval of the local ethics committee and was therefore performed in accordance with the ethical standards laid down in the 1964 Declaration of Helsinki and its later amendments. Adult patients who had been followed up in our clinic under treatment with IL-1 antagonists were evaluated with regard to whether they had a TBC infection before and after these treatments and whether they had been screened for latent TBC infection before IL-1 antagonist treatment and received prophylaxis. Clinical and laboratory data were obtained from hospital records and via telephone interviews after the patients had given their verbal consent to participate.Results Fifty-nine patients under IL-1 antagonists were consecutively enrolled. 58 were under follow-up with the diagnosis of familial Mediterranean fever and one patient with a diagnosis of adult-onset Still’s disease. 35 patients (59.3%) were treated with anakinra and 24 (40.7%) were treated with canakinumab. 12 (50%) of the canakinumab users had previously received anakinra treatment and were switched to canakinumab due to side-effects or ineffectiveness. The number of patients who underwent latent tuberculosisc infection (LTBI) screening before treatment was 37 (62.7%); the number of patients who received prophylaxis was 13 (22%). None of the patients receiving IL-1 antagonists developed active tuberculosis.Conclusion Blocking the IL-1 pathway may be safe regarding the activation of LTBI or development of a new tuberculosis infection even in locations with a high geographical risk.
Keywords: tuberculosis; familial Mediterranean fever; reactivation; autoinflammatory; interleukin-1